Positioning Sudirman Street, Bandung, as a Muslim-Friendly Cultural Tourism Destination: Trends, Strategies, and Challenges - Andreas Suwandi; Muktiarni; Endah Fitriyani (NHI HOSPITALITY INTERNATIONAL JOURNAL, 2024)
Purpose of the study: This study aims to explore the global development of halal tourism by examining its underlying concepts and principles, identifying key opportunities and challenges, and assessing Indonesia’s strategic positioning, particularly Bandung as an emerging halal tourism destination in response to growing Muslim tourist demand. Design/methodology: The research employs a qualitative, desk-based review approach, synthesizing secondary data from academic literature, industry reports, and policy documents on halal tourism development across multiple countries. The analysis focuses on comparative case studies of Muslim-majority and non-Muslim-majority nations, with specific attention to Indonesia’s national and local initiatives in promoting halal-friendly destinations. Findings: Halal tourism has evolved into a significant segment of the global halal economy, driven by rising Muslim populations, increased disposable incomes in Islamic countries (notably in the Middle East), and shifting lifestyle preferences. Countries worldwide are increasingly adopting halal tourism frameworks to capture this market. Indonesia, leveraging its cultural diversity, natural attractions, and Muslim-majority identity, is actively developing multiple regions including Bandung as competitive halal tourism hubs. However, challenges remain in standardization, certification, infrastructure readiness, and balancing religious compliance with mass tourism appeal. Research limitations/Implications: As a conceptual and descriptive study based on secondary sources, this research does not include empirical data from tourists or industry stakeholders. Future studies should incorporate primary data through surveys or interviews to validate findings and assess visitor satisfaction, destination competitiveness, and economic impact. The implications highlight the need for coordinated policy, private-sector investment, and community engagement to fully realize halal tourism potential. Novelty/Originality of the study: This article provides a timely synthesis of global halal tourism trends with a focused lens on Indonesia’s and Bandung’s emerging role, offering a structured overview that bridges theoretical concepts with practical destination development strategies in a rapidly growing market segment.